A review of calculating procedures on daylight factor based metrics under various CIE Standard Skies and obstructed environments. (1st February 2017) - Li, Danny H.W.; Lou, Siwei; Ghaffarianhoseini, Amirhosein; Alshaibani, Khalid A.; Lam, Joseph C.
Abstract: Prediction of the daylight level for any point within an indoor space is important in daylighting analysis. Recently, the International Commission on Illumination (CIE) has adopted a range of 15 standard skies covering the whole probable spectrum of usual skies found in the world. In densely-built urban cities, the exterior obstructions may substantially reduce the amount of daylight entering to the building interior. Through exhaustive investigations, we proposed various daylight computation tools for buildings under different obstructed overcast and non-overcast skies. This paper reviews the daylight factor (DF) based metrics and gives an overview of the latest dynamic daylight metrics, and generalizes the calculation procedures for estimating the internal daylight under the unobstructed and obstructed 15 CIE Standard Skies. The merits and limitations of the calculating procedures on DF-based metrics are discussed. The findings could be globally adopted and useful to students and building professions conducting daylighting studies and designs. Highlights: Different components for estimating interior daylight illuminance were established. The approach to compute SC and ERC for an interior horizontal point was proposed. The point DF, VDF and ADF can then be determined for further analysis.